EXPLORING SARCASM EXPRESSIONS USED AMONG SUMBAWANESE SPEECH COMMUNITY - Khairun Nufus; Mahyuni; Henny Soepriyanti; Untung Waluyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the use of sarcasm across different social contexts within the Sumbawanese speech community. The study used the Pragmatic Models: Conversational Implicature by Grice (1967, 1975; Grundy, 2000) theory. The sources of the data in this research were the daily conversations of Sumbawa people. The data was collected by doing procedures such as observations, interviews, notes, recording, books, and more. The data was analyzed by using thematic coding with following steps: identifying, classifying, describing, and giving conclusion. The result of this study showed that Sarcasm is an important aspect of communication in Sumbawa, and it is often used to criticize, ridicule, or mock someone's bad behavior. It can also be used to give advice or to humorously comment on a situation. Animal imagery, descriptions of human physical appearance, references to nature, and attitudes toward human behavior are all common elements of Sumbawan sarcasm. The context in which sarcasm is used varies, with different styles and approaches used in the family, society, and the work environment.